Espaces poétiques des mégalopoles-nécropoles - Por, Peter (Verbum – Analecta Neolatina, 2014)
This paper studies the emergence of a topos central tomodern poetry, and defines its mains characteristics: the megalopolis is the paradigmatic space of modern modern poetical existence. The Swan, by Baudelaire, is its seminal artwork, followed by three great compositions: The Musiscian of Saint Merry by Apollinaire, The Waste Land by T. S. Eliot, and Rilkes Tenth Duino’s Elegy. Each one of those poems is shaped on the pseudo-epical framework of the poet’s long going through, during which he he discovers the multiplicity of real characters, objects and places, which lead him to the opposite and fatal recognition: the megalopolis is a necropolis, the space of incongruity, emptiness and unreality. Each poem leads to a cosmical vision, but one which is an endless walk towards non-existence. As a conclusion, we underline two fundamental features of the creation of the poetical space: it is always voluntary, and it can only be accomplished through the use of temporary categories.